2006
DOI: 10.1016/j.jsgi.2006.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 3 Expression in Human Fetal Membranes and its Up-regulation by Cyclic Adenosine Monophosphate in Amnion Epithelial Cell Culture

Abstract: This study provides evidence of AQP3 expression in human fetal membranes and demonstrates that AQP3 expression in primary human amnion cell culture is up-regulated by second-messenger cAMP. As AQP3 is permeable to water, urea, and glycerol, modulation of its expression in fetal membranes may contribute to AF homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 23 publications
(4 reference statements)
5
32
0
1
Order By: Relevance
“…Saadoun et al (2005) demonstrated that AQP1 promotes cell migration in epithelial cells from wild-type mice as compared to AQP1-null mice. We also demonstrated that increasing concentrations of cAMP have a stimulatory effect on AQP1 which extends our previous studies showing that cAMP stimulated both AQP8 in human amnion-derived WISH cells (Wang et al, 2003) as well as AQP3 in primary human amnion cell cultures (Wang et al, 2006). Together, these data provide strong evidence that AVP at a physiological concentration may play a role in water balance in placental trophoblasts cells by acting through a cAMP signaling pathway to increase AQP1 expression.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Saadoun et al (2005) demonstrated that AQP1 promotes cell migration in epithelial cells from wild-type mice as compared to AQP1-null mice. We also demonstrated that increasing concentrations of cAMP have a stimulatory effect on AQP1 which extends our previous studies showing that cAMP stimulated both AQP8 in human amnion-derived WISH cells (Wang et al, 2003) as well as AQP3 in primary human amnion cell cultures (Wang et al, 2006). Together, these data provide strong evidence that AVP at a physiological concentration may play a role in water balance in placental trophoblasts cells by acting through a cAMP signaling pathway to increase AQP1 expression.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore incubation with 8-bromo-cAMP or direct 8-bromo-cAMP injection into oocytes expressing AQP1 cRNA significantly increased membrane permeability to water, suggesting that stimulation of AQP1 activity by AVP involves a cAMP-dependent mechanism (Patil et al, 1997). Previous work in our laboratory demonstrated that AQP3 is stimulated by cAMP agonists in human amnion cultures (Wang et al, 2006) suggesting a role for this molecule in amniotic fluid homeostasis. Since the placenta may have a role in amniotic-fetal water homeostasis through AQP regulation, the modulation of these AQPs in the placenta may be influenced by the level of AVP or cAMP in this organ.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Transcellular movement of water and solutes across the membranes during pregnancy, the intramembranous pathway, is a major pathway of fluid transport, in which aquaporin channels play a primary role [10]. Of the 13 currently recognized aquaporin water channels, aquaporins 1, 3, 8, and 9 have all been identified within the human placental unit [36,[57][58][59]. Wang et al [36] performed a series of in vitro studies demonstrating aquaporin 9 mRNA expression in human amnion, chorion, and placenta.…”
Section: Normal Pregnancy and Aquaporinmentioning
confidence: 99%